Effect of Altitude on Metabolic Syndrome - Bhatt, Mahendra Prasad; Poudel, Manavi; Pokhrel, Sushant; Kadel , Anuradha; Joshi, Mukesh (Journal of Nepal Health Research Council, 2025)
Background: Metabolic syndrome is a constellation of overweight/obesity, hypertension, and disturbances in lipid and carbohydrate metabolism. Hypoxic and hypobaric conditions of high altitude alter the use of energy producing metabolic fuels which may secondarily affect lipid and blood glucose concentrations. Thus, this study aims to assess prevalence and risk factors of the metabolic syndrome in high and low altitude inhabitants of Nepal. Methods: A hospital based descriptive cross-sectional study was carried out including 58 individuals from high altitude and 58 individuals from low altitude attending Manmohan Memorial Teaching Hospital, Kathmandu. Anthropometric measurements and blood pressure were recorded and blood samples were obtained for laboratory analysis. The samples were analyzed for fasting glucose, triglycerides, total cholesterol, high density lipoprotein cholesterol and low density lipoprotein cholesterol as per the standard guidelines. Results: Among the study group, 31.8% of high altitude and 68.2% of low altitude are found to have metabolic syndrome according to National Cholesterol Education Program Adult Treatment PlanIII and 35.5% of high altitude and 64.5% of low altitude are found to have metabolic syndrome according to HJSS criteria. The most prevalent defining components were low high density lipoprotein cholesterol (38.8%), high triglyceride (36.2%), elevated fasting blood sugar (33.6%) and Hypertension (34.4%). Among the lifestyle factors, alcohol consumption, unhealthy diet and physical inactivity were found to be an independent risk factors for MetS. Conclusions: High altitude inhabitants have significantly lower metabolic syndrome than that of low altitude inhabitants because of less physical activities in their work and sedentary. Thus, encouragement of food habit, healthy lifestyle, and timely health screening and monitoring help in prevention of metabolic syndrome. Keywords: Altitude; diabetes mellitus; early diagnosis; metabolic syndrome; prevention.